Answer:
Option (D) is correct.
The solution of the quadratic equation
is
and
.
Explanation:
Consider the given quadratic equation
![5z^2-9z-2=0](https://img.qammunity.org/2020/formulas/mathematics/high-school/d6t0ryh1irqv4hophbwiduo6gf4ay8jghu.png)
We can solve a quadratic equation using middle term splitting method,
-9z can be written as -10z+z
thus, the equation becomes,
![5z^2-10z+z-2=0](https://img.qammunity.org/2020/formulas/mathematics/high-school/30s5vmgp0u3g61vn99de43siwlrr3iqczw.png)
Taking factors common, we get,
![\Rightarrow 5z(z-2)+1(z-2)=0](https://img.qammunity.org/2020/formulas/mathematics/high-school/5k7tdfam7a89xv4qxewgmgslgysysd3y12.png)
![\Rightarrow (5z+1)(z-2)=0](https://img.qammunity.org/2020/formulas/mathematics/high-school/zou593amjg4huva1yvdgr16x6tdagcl4ng.png)
or
![\Rightarrow (z-2)=0](https://img.qammunity.org/2020/formulas/mathematics/high-school/z524y10gwvemxic5ydjksmpwn0gdx4pvua.png)
or
![\Rightarrow z=2](https://img.qammunity.org/2020/formulas/mathematics/high-school/1m47gfrg97v6moxhwe0sxdkpjkoessx4p5.png)
Thus, the solution of the quadratic equation
is
and
.